A categoria tempo na escrita de alunos surdos sinalizantes de Libras - Mendonça, Jeane Maria Alves de (2021)
Through a functionalist perspective, this thesis examines the time and aspect categories in the writing of deaf sign language users. The objectives that guided this research were: a) to map the verbal tenses encoded in the narrations and dissertations produced in Portuguese by deaf students; b) to examine prototypical linguistic and extralinguistic factors conditioning the marking of the category of time. The theoretical assumptions of North American Linguistic Functionalism (HOPPER; THOMPSON, 1980; GIVÓN, 1995) and the postulates on the acquisition of a second language advocated by Selinker (1972); Mclaughlin, (1978) and Krashen (1985) were adopted to support this work of research. This research analyzes language data from 22 texts written by deaf undergraduates in the Language Studies-Brazilian Sign Language (Libras) course at the Federal University of Ceará, Brazil. The data consist of eight narrative texts (personal accounts) and fourteen essays (opinion articles), from which were mapped a total of 239 pieces of data. This material was, then, analyzed according to the following basic notions: the relationship between foreground and background, the parameters of transitivity – these first two according to Hopper and Thompson (1980) – and the compositional aspect of the forms – according to Wachowicz (2003) and Bardovi-Harlig (1995). Furthermore, we investigated the extralinguistic factors that condition the choice of verbal tense: age group in which Libras was acquired, based on Quadros (2008); signaling level of parents or guardians, according to Finau (2008) and the modality of teaching in Basic Education, according to Finau (2008). From the mapping, concerning to the time category marking, we found that the present tense predominated in 49% of the mapped forms, followed by the past tense, which represented 37% of the forms. While the future tense represented only 5% of the occurrences. Regarding the infinitive nominal form, which usually appears in textual productions in Portuguese by deaf sign language users because it approaches verbal coding in Libras, represented only 9% of the occurrences, a fact that implies that the observed students may have good command of the interlanguage. In the figure clauses and in the clauses with high transitivity, the simple past tense predominated in the narrative texts, while the simple present tense predominated in the essays. In the other clauses - background 1, background 2, clauses with medium and low transitivities - in both types analyzed the highest frequency was that of forms encoded in the present, followed by forms in the past tense, and forms in the infinitive. Finally, there was the occurrence of coded forms in the future tense. Regarding the compositional reading of the aspect, we found that the morphology of the verb does not always correspond to the internal tense of the clause, which demonstrates the importance of considering the whole context. When analyzing the extralinguistic control factors, these were not relevant in the marking of the category. However, we cannot fail to highlight the importance for deaf children of acquiring their L1 or Libras early, of growing up in an environment in which guardians or parents can use sign language, and of attending a bilingual school for their Basic Education.